Hubungan C-Reaktif Protein dan Kondisi Udara Tercemar PM10 Dengan Lama Menetap Lansia (Studi Kasus di Kelurahan Kampung Lalang Kota Medan Tahun 2013) - Sumihar Pasaribu; Hidayati Hidayati; Syafruddin Ilyas (Jurnal Pendidikan Kimia (JPKim), 2015)
Abstract. The decrease in air quality has long been a public health problem, particularly in the industrialized countries that has many factories and motor vehicles. The high level of air pollution in the city will affect human health in the city, and will ultimately reduce the quality of human life. The Medan city air quality periods 2011-2012  recorded data show that at Terminal Pinang Baris passed the quality standard of 150 μg/m3 for PM10 according to national standar in PP.No.41 1999. There is still plenty of evidence of the extent to which exposure to particulate matter is associated with changes in the level of systemic inflammation in the general population in the city of Medan. Exposure to air pollution is associated with increased levels of C-Reactive Protein (CRP) is believed to trigger systemic inflammation. Particle Matter (PM10) is the pollutant in the air resulting from the activity of motor vehicles, has a relationship with an increase in C-Reactive Protein. Ultimately will lead to various diseases in humans at all age levels. In cross-sectional study was conducted on 50 elderly volunteers who have been residing more than 3 years and close to the center of the air pollution in the this location. After obtaining approval from the ethics committee, then covers anamneses examination, physical examination and venous blood samples for CRP concentrations examined in the laboratory. Research result show that there are relationship between long-time resident with increasing concentrations of CRP for the elderly with statistical chi-square test and Fischer exact test. It is implies that this case enhancement factors for coronary heart disease risk in elderly residing in the study area. Keywords: CRP, long-time resident, PM10, elderly